Analisis Strategi Pengembangan SDM untuk Meningkatkan Mutu Pendidikan dan Minat Calon Siswa SMAN 11 Denpasar - Tika Purnama Wati, Ni Komang Gek; Irma Yunita, Putu (As-Syirkah: Islamic Economic & Financial Journal, 2025)
Education is a key pillar in developing quality human resources. Schools, as formal educational institutions, play a strategic role in creating a competent and virtuous future generation. However, in the era of globalization and increasingly fierce competition, schools are required to continuously improve the quality of education and their competitiveness. The issue of facilities and infrastructure is one of the critical factors influencing prospective students' interest in enrolling at SMA Negeri 11 Denpasar. An interview with the Principal, I Ketut Suwita, S.Pd., M.Pd., revealed that "the incomplete condition of laboratories, fields, and libraries, as well as the inadequate school grounds, are challenges for us in improving the quality of education at SMA Negeri 11 Denpasar." This study used two types of data to gain a comprehensive understanding. The research method used was a qualitative and quantitative approach. Based on the results of the study, the decline in prospective student interest in SMA Negeri 11 Denpasar was influenced by a combination of internal and external factors. Internally, the school is still new and therefore does not have a strong track record and brand equity. Facilities such as laboratories, projectors, and sports fields are still limited, and digital promotion strategies are not optimal. Externally, social perceptions, prestige factors, and PPDB dynamics make people tend to choose schools with established reputations.